Feng Shui superstitious belief: does it influence young generations in housing purchase intention? - Hassan, Mohammad Mujaheed; Tedong, Peter Aning; Haris Fadzilah, Asmaul Husna (Malaysian Institute of Planners, 2023)
Superstition is an indispensable part of every ethnic culture in Malaysia. Each race has its own culture and its own superstitions. This is certainly true in the multicultural landscape of Malaysia. Since superstition is part of daily life, it can even have an impact on the housing property market. This article aims to examine the superstitious beliefs in Feng Shui of the young generation’s intention to buy a house. This study focuses on the young generation with the prime working-aged between 25 and 40 years old in the Klang Valley. This study uses quantitative methods. A total of 2,600 questionnaires were distributed, however, only 97% or 2523 questionnaires are valid to proceed for data analysis.   In summary, there is a significant correlation between the influences of superstition beliefs on the willingness of a young one to buy a house. Superstition is affecting the decision-making process of the Chinese community.